Multicultural analysis of websites of the european national public collection - Losonczi, György (Studia Mundi – Economica, 2016)
The European Union is a truly multilingual institution that fosters the idealof a single Community with a diversity of cultures and languages, as a prescriptive term: multiculturalism. This paper will examine, which languages are supported by the websites of the national public collection institutions in the EU, is there a correlation between a country's ethnic, tourist data and institutions of the European Union's official languages. In other words, I attempt to derive aggregate transaction data by country to define multiculturalism term of linguistic aspects of public collections.